THE OUTSIDER. - Rose, Matthew (First Things: A Monthly Journal of Religion & Public Life, 2019)
The article presents the author's comments on conservative thinker and activist Samuel Francis, who was a critic of the American conservatism. The author mentions how Francis' essays were published in small-circulation journals and his attacks on globalism admired by paleoconservative right-wing people. The author calls his essay "Principalities & Powers," as the Trumpist manifesto that no one had been able to formulate.